Persepsi Petani terhadap System Of Rice Intensification (SRI) di Subak Yeh Anakan, Kecamatan Negara, Kabupaten Jembrana - I KADE NOPA SASTRA WIRAWAN; I DEWA PUTU OKA SUARDI; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Farmers’ Perception on the System of Rice Intensification (SRI) in Subak Yeh Anakan, Negara District, Jembrana Regency The need for the agricultural sector is increasing; various policies have been taken by the government to increase rice production in Indonesia. SRI is one approach to rice cultivation practice that emphasizes the management of soil, plants, and irrigation water through the group empowerment based on environmentally-friendly activities. The purpose of this study was to determine the perception of farmers on SRI in Subak Yeh Anakan, in Jembrana Regency. The scope of this research was the study of the perception of one of the central government programs namely SRI which is located in the district of Negara. This study used qualitative descriptive analysis. Based on the survey results, it was revealed that the perception of farmers on SRI in Subak Yeh Anakan was classified into good category by achieving a score of 76.76%. For the development of the SRI programs in Subak Yeh Anakan to be sustainable, it is suggested that the Government of Jembrana through the Department of Agriculture and Forestry should more intensively provide guidance to farmers and agricultural extension personnel should develop technical extension that can encourage farmers to adopt SRI independently.